Managing and Controlling Extrabudgetary Funds - Radev, Dimitar; Allen, Richard (Washington, D.C. : International Monetary Fund, 2006)
This paper addresses issues relating to the establishment and financial management of extrabudgetary funds (EBFs), a large group of government entities that on average accounts for 40 to 45 percent of central government expenditure-two-thirds of which represents social security funds-in countries at various stages of development. If improperly designed and managed, EBFs can undermine effective fiscal control. However, they also bring potential benefits in the form of greater autonomy of decision-making in countries with well-established governance and financial management systems that have applied the "agency model" of devolved public management and fiscal control. The paper develops a typology of EBFs and argues that EBFs are frequently created because of failures in the budget system and political economy factors that need to be recognized and, where possible, corrected. The paper recommends that data on EBFs be consolidated within a unified system of fiscal reporting and proposes an analytical framework that governments might use to evaluate the effectiveness and utility of their EBFs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet